Implementasi Sistem Informasi Rental PlayStation Berbasis Real-Time dengan Fitur Status Unit dan Estimasi Waktu Penggunaan - Roys Pakaya (Journal Of Software Engineering And Communication, 2026)
The advancement of information technology has driven digital transformation across various business sectors, including PlayStation rental businesses, which generally still rely on manual reservation systems. This condition leads to several operational issues, such as uncertainty in unit availability, poorly organized customer queues, and limited information regarding the duration of use by other customers. In addition, the reservation process, which still depends on direct communication or social media, often results in delayed responses and miscommunication between customers and business owners. These challenges ultimately reduce service quality and time efficiency for both parties. This study aims to implement a real-time PlayStation rental information system capable of providing accurate and transparent information on unit status and estimated usage time. The methods employed include requirement analysis through user interviews, system design using a structured approach, and the development of an application prototype tailored to user needs. The developed system is equipped with key features such as unit status indicators (available, in use, and waiting), real-time remaining usage time estimation, and integrated management of transaction and customer data within the system. The implementation results indicate that the system improves service efficiency by delivering faster and more accurate information to customers. Furthermore, it reduces uncertainty in the reservation process, minimizes disorganized queues, and assists business owners in managing operations more effectively and systematically. Therefore, the developed information system serves as an effective and relevant solution for enhancing service quality and competitiveness in PlayStation rental businesses in the digital era.